2022
DOI: 10.1167/tvst.11.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Retinal Microvascular Abnormalities in Patients With Type 2 Diabetes Mellitus Without Clinical Sign of Diabetic Retinopathy

Abstract: Purpose To evaluate microvascular abnormalities in the macula and peripapillary area in diabetic patients without clinical signs of diabetic retinopathy (DR) and compare them with healthy control eyes, using optical coherence tomography angiography (OCTA). Methods A prospective study was performed of 49 eyes from 49 diabetic patients without clinical signs of DR and a control group of 52 eyes from 52 healthy normal individuals. The 3 × 3 mm macular scans and 4.5 × 4.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
2
1
0
1
Order By: Relevance
“…We also found the 300 μm surrounding the FAZ to be the most important area of capillary change in our cohort, which is consistent with a recent report by Han et al 41 who found the foveal density-300 to be the most useful biomarker for distinguishing patients with DM without DR from healthy controls. By partitioning this “foveal density-300” region into perivenular, periarteriolar, and capillary zones, we were able to distinguish the central perivenular deep capillary zone as the most significant biomarker for distinguishing patients with DM without DR.…”
Section: Discussionsupporting
confidence: 93%
“…We also found the 300 μm surrounding the FAZ to be the most important area of capillary change in our cohort, which is consistent with a recent report by Han et al 41 who found the foveal density-300 to be the most useful biomarker for distinguishing patients with DM without DR from healthy controls. By partitioning this “foveal density-300” region into perivenular, periarteriolar, and capillary zones, we were able to distinguish the central perivenular deep capillary zone as the most significant biomarker for distinguishing patients with DM without DR.…”
Section: Discussionsupporting
confidence: 93%
“…Taken together, these findings suggested that ultra-wide SS-OCTA has advantages when compared with FFA or 12 mm × 12 mm OCTA, with the potential to be a rapid, repeatable and noninvasive method for DR screening and follow-up. Studies using 3 × 3 mm OCT and OCTA devices have found no significant differences in the VD and thickness of the superficial and deep retinal layers between DM and NC groups (25)(26)(27), findings partially consistent with the results of the present study. In contrast, other studies have found that the VD and thickness in the parafoveal and/or perifoveal layers are significantly lower in patients with DM than in NCs (28)(29)(30).…”
Section: Discussionsupporting
confidence: 92%
“…Studies using 3 × 3 mm OCT and OCTA devices have found no significant differences in the VD and thickness of the superficial and deep retinal layers between DM and NC groups ( 25 27 ), findings partially consistent with the results of the present study. In contrast, other studies have found that the VD and thickness in the parafoveal and/or perifoveal layers are significantly lower in patients with DM than in NCs ( 28 30 ).…”
Section: Discussionsupporting
confidence: 92%
“…Ein gutes Beispiel ist der Diabetes mellitus. Beim Diabetes mellitus ohne diabetische Retinopathie kommt es bereits in 40,4% zu mikrovaskulären Auffälligkeiten mit Vergrößerung der fovealen avaskulären Zone (32,5%), zu nicht perfundierten Arealen und zu Mikroaneurysmen in den oberflächlichen und tiefen retinalen Schichten (7 – 13%) 58 , 59 , 60 . Mit zunehmendem Schweregrad der diabetischen Retinopathie nehmen diese mikrovaskulären Störungen zu 61 .…”
Section: Einfluss Des Diabetes Mellitus Auf Strukturell-anatomische U...unclassified
“…A good example is diabetes mellitus. Diabetes mellitus patients without diabetic retinopathy develop microvascular abnormalities in 40.4% of cases, with enlargement of the foveal avascular zone (32.5%), non-perfused areas, and microaneurysms in the superficial and deep retinal layers (7 – 13%) 58 , 59 , 60 . As the severity of diabetic retinopathy increases, these microvascular disorders increase 61 .…”
Section: Influence Of Diabetes Mellitus On Structural Anatomical Exam...mentioning
confidence: 99%